Persepsi Caring Mahasiswa Keperawatan - Pragholapati, Andria; Hidayati, Eni (Yayasan Healing and Healthcare Education, 2023)
Nursing is an art and a science based on knowledge of professional care. Thus, examination of how students perceive care can improve the way these concepts are taught and learned in nursing. Objective: To describe Caring perceptions among undergraduate nursing students. The perception of caring among undergraduate nursing students is a dynamic phenomenon that is modified throughout the nurse education process. Academic year, previous work experience in the health field and type of access to university influenced students' perceptions of caring.